O aluno dos anos finais do ensino fundamental (da escola pública) com grande defasagem em relação às habilidades para a leitura e a escrita: investigando sujeitos e contextos - Pereira, Gilvan Elias (2011)
Based on a perspective that assumes a direct relationship between linguistic competence and success or failure at school, this research turns to the student in situation of failure and that has in low language competence (not the ability to make use of language in real situations of life, but to meet the demands required by the school) a central difficulty impeding academic success. To meet such a student in order to better understand what is behind the "alarming" statistics of school failure, we took into account the weight that language has when it comes to school and school learning and, therefore, the resulting need to consider the complexity of the relationship between school learning (in relation to knowledge) an language. It has been assumed that each student excluded or in situations of failure, has his own history is strongly marked, among other things, by the barriers that the low level of language proficiency has imposed. Results of the research (case study) conducted among students in situation of failure confirmed, therefore, that the stigma of student who does not learn, who cannot read and write with the skills required by the school but even so remains there on the edge of her "illiteracy" represents a small part of the qualitative picture of the excluding and selective school model still very present in Brazilian society and that should not be understood only by the logic of statistics or theories based on the exclusive assumption of social modeling